Comparative Study of Uzbek and Korean Folk Games - Tojiboyeva Dilovar; Jabbor Eshonqulov (International Journal on Integrated Education, 2022)
The subject of the comparative study of Uzbek and Korean folk games mainly reveals the side of the interdependence of folk games. The influence of our folk games, which are passed down from generation to generation, on the minds of young people, attracting them to our national values and guiding them in the right direction in life and the importance of games to health is stated to be useful. In the current conditions, the main task of Uzbek folk games is to ensure the education of children in accordance with the requirements of our society with its content and method, to develop moral and voluntary qualities in them, to form the skills and qualifications of creators and creators, and patriotic qualities. In the ancient system of education, games were widely used as a means of personality formation